Rediseño y Construcción De Componentes mecánicos Para La habilitación De Sillas De Ruedas En La Fundación Casa De La Esperanza (Sede Cajicá). (2022)
In the current work, the design and reconstruction of three wheelchairs, disassembled and incomplete, which were originally electric, is presented with a series of analyzes and with the help of Autodesk Inventor software, it is guaranteed that the redesign is reliable, taking safety into account, ergonomics and current standards